Osmotic Dehydration of Sliced Pears - Sharma, H K; Pandey, H; Kumar, P (Journal of Agricultural Engineering, 2003)
Mass transfer changes were evaluated in the processing of pears by osmosis. Water loss, solid gain and mass loss were found to be directly affected by the concentration of syrup and proportion of syrup with respect to fruit. Change in syrup concentration from 35 to 45degree brix with a fruits to syrup ratio of 1:2 resulted in more significant percentage changes: 18.09 to 23.18 in water loss, 9.26 to 20.06 in mass loss and 13.59 to 16.38 in solid gain, respectively. For all concentrations, water loss was favored over solid gain, thereby, causing mass loss of samples.